Processing Branches: Reactivating the Performativity of Natural Wooden Form with Contemporary Information Technology. (June 2014) - Schindler, Christoph; Tamke, Martin; Tabatabai, Ali; Bereuter, Martin; Yoshida, Hironori
Angled and forked wood – a desired material until 19th century, was swept away by industrialization and its standardization of processes and materials. Contemporary information technology has the potential for the capturing and recognition of individual geometries through laser scanning and computation and subsequently design and bespoke CNC fabrication. The question whether this allows for a new approach to the uniqueness that is offered to us by nature is discussed in a series of workshops and projects, which explore the performative potential of naturally grown materials.